Rapid changes in neuroendocrine regulation may contribute to reversal of type 2 diabetes after gastric bypass surgery - Katsogiannos, Petros; Kamble, Prasad G.; Wiklund, Urban; Sundbom, Magnus; Espes, Daniel; Hammar, Ulf; Karlsson, F. Anders; Pereira, Maria J.; Eriksson, Jan W. (Endocrine, 2020)
Objective To explore the role of hormones and the autonomic nervous system in the rapid remission of diabetes after Roux-en-Y Gastric Bypass (RYGB). Research design and methods Nineteen obese patients with type 2 diabetes, 7 M/12 F, were randomized (2:1) to RYGB or standard-of-care medical treatment (control). At baseline and 4 and 24 weeks post surgery, fasting blood sampling, OGTT, intravenous arginine challenge, and heart-rate variability (HRV) assessments were performed. Results At both 4 and 24 weeks post-RYGB the following effects were found: arginine-stimulated insulin secretion was reduced. GLP-1, GIP, and glucagon rise during OGTT was enhanced. IGF-1 and GH levels increased. In addition, total HRV and spectral components P LF (power of low frequency) and P HF (power of high frequency) increased. At 4 weeks, morning cortisol was lower than baseline and 24 weeks. At 24 weeks, NEFA levels during OGTT, and the P LF / P HF ratio decreased. None of these changes were seen in the control group. Conclusions There were rapid changes within 4 weeks after RYGB: signs of enhanced parasympathetic nerve activity, reduced morning cortisol, and enhanced incretin and glucagon responses to glucose. The findings suggest that neurohormonal mechanisms can contribute to the rapid improvement of insulin resistance and glycemia following RYGB in type 2 diabetes.